UI/UX Mobile Games Transformation towards Translated Language: Case Study : Ragnarok Mobile Eternal Love - Andreas Kurniawan; Hervina Dyah Aprilia (Bina Nusantara University, 2018)
The purpose of this research study is to get data of user experience towards mobile game design and the transformation of its interface due to translated language. Most of popular mobile games came from China with their local language and writing system. Chinese alphabetic is appropriate for vertical or horizontal orientation, but English and Indonesian alphabetic are not appropriate with vertical orientation. Ragnarok M: Eternal Love with MMORPG’s genre is the game sample model, originally from China server and now this game is translated into several languages such as English and Bahasa Indonesia. Ragnarok M: Eternal Love’s game developer used a unique method with combined icon and text in order to solve layout’s problem that they encounter when converted in to several languages. We conduct the experiment within 2 period of time, based on 25 participants (gamer), all participants tried user interface from a game model sample. The result confirmed that the display of the UI (user interface) used by the developer team of Ragnarok M: Eternal Love, had demonstrated a good solution in developing a user interface for mobile game, when confronted by fixed layout and forced to adapt to various different language, but it still need some adjustment time to fully understand the function of every button.